2022
DOI: 10.1007/s40123-022-00509-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of Imaging Technology to Assess the Effect of COVID-19 on Retinal Tissues: A Systematic Review

Abstract: Purpose To evaluate the effect of COVID-19 on retinal tissues by conducting a systematic review and meta-analysis of the current literature. Background The novel coronavirus disease is not yet well understood. The orbit provides a window into the body's microvasculature, and as such, it is a non-invasive opportunity to analyse the systemic circulation in vivo. By analysing the current literature, we test the hypothesis that non-invasive imaging of the retina could provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Previous studies have pointed to retinal involvement in COVID-19, such as central retinal artery/vein occlusion and acute macular neuroretinopathy, which can directly damage vision [ 10 , 11 , 18 ]. RGCs are particularly susceptible to SARS-CoV-2 infection, which can directly cause acute pathological changes and increase overall retinal thickness due to immune cells infiltration [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have pointed to retinal involvement in COVID-19, such as central retinal artery/vein occlusion and acute macular neuroretinopathy, which can directly damage vision [ 10 , 11 , 18 ]. RGCs are particularly susceptible to SARS-CoV-2 infection, which can directly cause acute pathological changes and increase overall retinal thickness due to immune cells infiltration [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…RGCs are particularly susceptible to SARS-CoV-2 infection, which can directly cause acute pathological changes and increase overall retinal thickness due to immune cells infiltration [ 19 , 20 ]. Mechanistically, the viral infection induces a procoagulant state and endothelial inflammation with recruitment of inflammatory cells, resulting in micro-thrombosis and retinal thickening in the early stage [ 10 , 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review in 2022 suggested the potential involvement of the posterior segment in SARS-CoV-2, either in the initial or later stage 9 . However, few studies have systematically described the manifestations of the posterior segment of the eye by multimodal imaging study 10 .…”
Section: Introductionmentioning
confidence: 99%
“…the initial or later stage 9 . However, few studies have systematically described the manifestations of the posterior segment of the eye by multimodal imaging study 10 .…”
mentioning
confidence: 99%